Dampak Liberalisasi Perdagangan terhadap Efiiensi Teknis Perusahaan pada Industri Manufaktur Indonesia - Nurrahma, Tsurayya (UI Scholars Hub, 2013)
Having data sample in 1987, 1995, and 2008, this research aims to analyze the impact of trade liberalization on technical efficiency of Indonesian manufacturing firms since deregulation in the 1980s. In addition, the research also analyzes the impact of other efficiency determinants coming from firm characteristics and market structure. Technical inefficiency score is estimated by using stochastic production frontier model, whereas the impact of efficiency determinants is analyzed by using Ordinary Least Squared model (OLS). For each year observed, liberalization has different impacts on technical efficiency. However, as liberalization continues, it has facilitated firms to produce towards their full technical efficient production-level.